2019
DOI: 10.1111/bju.14673
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy, clinical utility and influence on decision‐making of a methylation urine biomarker test in the surveillance of non‐muscle‐invasive bladder cancer

Abstract: ObjectivesTo investigate prospectively the clinical utility and influence on decision-making of Bladder EpiCheck TM , a non-invasive urine test, in the surveillance of non-muscle-invasive bladder cancer (NMIBC). Materials and MethodsUrine samples from 440 patients undergoing surveillance for NMIBC were prospectively collected at five centres and evaluated using the Bladder EpiCheck test (NCT02647112). A multivariable nomogram and decision-curve analysis (DCA) were used to evaluate the impact of Bladder EpiChec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 26 publications
1
55
3
Order By: Relevance
“…The high NPV reported by previous studies could not be reached in our study (97%, 95.1%, and 94.4% vs 82.9%, respectively). The PPV in our study was superior to that reported by Witjes et al (68.2% vs 48.8%) but was not reported by Wassermann et al and thus cannot yet be discussed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The high NPV reported by previous studies could not be reached in our study (97%, 95.1%, and 94.4% vs 82.9%, respectively). The PPV in our study was superior to that reported by Witjes et al (68.2% vs 48.8%) but was not reported by Wassermann et al and thus cannot yet be discussed.…”
Section: Discussioncontrasting
confidence: 99%
“…The specificity reported by Wasserstrom et al was 83%, and that in the studies by Witjes et al and D'Andrea et al was 88%, whereas the specificity in our study was 86.3%. However, the test could not reach the excellent specificity of cytology (98%) but nonetheless performed in an excellent way.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…No gender limit was considered. Two studies [10,11] included only patients with NMIBC resected within the previous 12 months.…”
Section: Types Of Participants Includedmentioning
confidence: 99%
“…Particularly, for cytological specimen classification, all studies used the Paris System for Reporting Urinary Cytology. During three of the studies [10,11,17] the wash cytology was considered 'negative' when the result was 'negative for high-grade urothelial carcinoma (HGUC)' and 'atypical urothelial cells', whereas 'suspicious for HGUC', 'HGUC', and 'low-grade (LG) intraepithelial neoplasia' were clustered as 'positive'. Concerning the case of positive spontaneous or wash cytology with negative cystoscopy and/or histology, the reference standard was evaluated at the subsequent follow-up cystoscopy with multiple random biopsies or targeted biopsies on a suspicious area [17].…”
Section: Reference Standard Definition and Follow-upsmentioning
confidence: 99%